Data on chief financial officer attributes and risk management strategies for Nigerian listed financial institutions - Alex Adegboye; Stephen A. Ojeka; Kofo Adegboye; Oluwaseyi Alabi; Mosinmileoluwa Afolabi; Francis Iyoha (Data in Brief, 2019)
This data article is related to the research article “Chief Financial Officer Roles and Enterprise Risk Management: An Empirical Based Study” Ojeka et al. (2019). The study explores the impact of CFO roles on the execution of ERM strategies sampled with Nigerian financial institutions for the period of 2013–2017. The study develops three distinct indexes representing the CFO roles namely CFO power, CFO experience and CFO knowledge via principal component factoring. The study also measures ERM components simultaneously to capture the extent of sophisticated ERM system. This article presents the data collected from 33 financial companies listed on Nigerian stock exchange. The data were extracted from the annual reports of the sample companies using quantitative content analysis about Enterprise Risk Management, Chief Finance Officer Roles and Firm level data. Keywords: Data, CFO characteristics, Enterprise risk management, Firm characteristics